Digest of Technical Papers. 11th IEEE International Pulsed Power Conference (Cat. No.97CH36127)
DOI: 10.1109/ppc.1997.674531
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum surface flashover and high pressure gas streamers

Abstract: Portions of this document may be illegible electronic image products. Images are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The elongation of the plasma plume when a target is present, even if it is a glass target with low-permittivity, might be caused by different gas mixing like discussed above, but it is probable that this is also an electrical effect of the target. The presence of a dielectric material, even with low-permittivity, has been shown to modify the dynamics with which the fast ionization waves travel [49][50][51][52][53][54][55]. The dielectric does not even have to be in the path of the ionization wave to modify its trajectory, it only has to be in its close vicinity [56].…”
Section: Electrical Properties Of the Targetmentioning
confidence: 99%
“…The elongation of the plasma plume when a target is present, even if it is a glass target with low-permittivity, might be caused by different gas mixing like discussed above, but it is probable that this is also an electrical effect of the target. The presence of a dielectric material, even with low-permittivity, has been shown to modify the dynamics with which the fast ionization waves travel [49][50][51][52][53][54][55]. The dielectric does not even have to be in the path of the ionization wave to modify its trajectory, it only has to be in its close vicinity [56].…”
Section: Electrical Properties Of the Targetmentioning
confidence: 99%
“…The question is, why is propagation over the dielectric surface faster than through the gas? Many scientists assumed that this is the result of the dielectric properties of the material [2][3][4][5][6][7][8][9][10]. Akyuz et al [7] suggested a combination of permittivity of the dielectric and accumulated negative charge on its surface was responsible for increase in the ionization rate on the dielectric surface, that speeds up the discharge.…”
Section: Average Speedmentioning
confidence: 99%
“…On the other hand, photoemission of electrons from the cathode or the dielectric surface can be viewed as a mechanism partly responsible for the fast propagation. Although it still has not been proven, photoemission of electrons from the dielectric surface is a concept proposed quite a few times already [2][3][4][5][6]. The area around the streamer tip is very active with different reactions such as ionization, excitations and deexcitations of argon atoms.…”
Section: Average Speedmentioning
confidence: 99%
See 2 more Smart Citations